Compatibility of Porous Chitosan Scaffold with the Attachment and Proliferation of human Adipose-Derived Stem Cells In Vitro - Gomathysankar, Sankaralakshmi; Halim, Ahmad Sukari; Yaacob, Nik Soriani; Mohd Noor, Norhayati; Mohamed, Mohaini (GN Corporation Limited, 2016)
Adipose-derived stem cells (ASCs) have potential applications in the repair and regeneration of various tissues and organs. The use of various scaffold materials as an excellent template for mimicking the extracellular matrix to induce the attachment and proliferation of different cell types has always been of interest in the field of tissue engineering because ideal biomaterials are in great demand. Chitosan, a marine polysaccharide, have wide clinical applications and it acts as a promising scaffold for cell migration and proliferation. ASCs, with their multi-differentiation potential, and chitosan, with its great biocompatibility with ASCs, were investigated in the present study. ASCs were isolated and were characterized by two different methods: immunocytochemistry and flow cytometry, using the mesenchymal stem cell markers CD90, CD105, CD73 and CD29. The ASCs were then induced to differentiate into adipogenic, osteogenic and chondrogenic lineages. These ASCs were incorporated into a porous chitosan scaffold (PCS), and their structural morphology was studied using a scanning electron microscope and hematoxylin and eosin staining. The proliferation rate of the ASCs on the PCS was assessed using a PrestoBlue viability assay. The results indicated that the PCS provides an excellent template for the adhesion and proliferation of ASCs. Thus, this study revealed that PCS is a promising biomaterial for inducing the proliferation of ASCs, which could lead to successful tissue reconstruction in the field of tissue engineering.